The Influence of Substrate Characteristics on Seagrass Distribution Patterns in The Coastal Waters of Bontang City, East Kalimantan - Jailani Jailani; Noorsheha Noorsheha; Nurfadilah Nurfadilah (Berkala Perikanan Terubuk, 2023)
This study aimed to examine the distribution, species composition and density of seagrass vegetation in the coastal waters of Bontang City, East kalimantan, spread across four disticnt locations, each with varying proximities to industrial areas and the beach. Sampling was conducted during the lowest tide, utilizing three 140 m transect lines at each site, directed towards the deeper reef shore, and spaced 200m apart, with seagrass vegetation sampling points marked at 20m intervals. A 1 x 1 m⁅ ⁆⁅2⁆⁅ ⁆2 aluminum wire frame was employed to assess the species composition, density, and distribution pattern of the seagrasses, following which the samples were identified. The characterization of each research location, based on substrate characteristics, was executed using Principal Component Analysis (PCA), while Correspondence Analysis (CA) with MINI-TAB 14 software was utilized to determine the relationship between substrate characteristics and seagrass species distribution at various locations. The study found a significant difference in seagrass abundance at one location compared to the others. The results revealed that E. acoroides exhibited H' = 2.9530 and E' = 0.7117. Subsequent tests yielded values of Location C = 7.0476, Location B = 6.8776, Location A = 4.2319, and Location D = 2.9105, and an LSD value = 1.586. This indicated that Location C did not significantly differ from Location B, yet was significantly different from the remaining locations. The research underscores the influence of substrate quality and proximity to industrial areas on seagrass distribution and density.